Laser ultrasonics system for measurement of speed of sound in gases - Sakamoto, J. M S; Pacheco, G. M.; Kitano, C. [UNESP]; Machado, H. A. (AIP Publishing, 2012)
In this work we developed a setup to measure the speed of sound in gases using a laser ultrasonics system. The mentioned setup is an all optical system composed by a Q-switched Nd:YAG laser to generate the sound waves, and a fiber optical microphone to detect them. The Nd:YAG provided a laser pulse of approximately 420 mJ energy and 9 ns of pulse width, at the wavelength of 1064 nm. The pulsed laser beam, focused by a positive lens, was used to generate an electrical breakdown (in the gas) which, in turn, generates an sound wave that traveled through a determined distance and reached the fiber optical microphone. The resulting signal was acquired in an oscilloscope and the time difference between the optical pulse and the arrival of the sound waves was used to calculate the speed of sound, since the distance was known. The system was initially tested to measure the speed of sound in air, at room pressure and temperature and it presented results in agreement with the theory, showing to be suitable to measure the speed of sound in gases. © 2012 American Institute of Physics.
Keywords: Fiber optical microphone; Laser ultrasonics; Speed of sound